O paradoksie Halla i rzucaniu monetą - Dniestrzański, Piotr; Wilkowski, Andrzej (On Hall’s paradox and coin flipping, 2009)
In this paper we analyses what the causes of intuition‟s failure are when it comes to probability. We try to indicate the points, in which appear the disorders of intuition, on the example of Monty Hall paradox, Penney`s game (based on flipping the coin) and also regular exercise of theory of probability
Didactics of Mathematics, 2009, Nr 5-6 (9-10), s. 43-52
Keywords: Hall`s paradox; Penney`s game